2009
DOI: 10.1002/adfm.200900253
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Tuned Properties for Electrolyte‐Free Carbon Nanotube Sheets

Abstract: Injecting high electronic charge densities can profoundly change the optical, electrical, and magnetic properties of materials. Such charge injection in bulk materials has traditionally involved either dopant intercalation or the maintained use of a contacting electrolyte. Tunable electrochemical charge injection and charge retention, in which neither volumetric intercalation of ions nor maintained electrolyte contact is needed, are demonstrated for carbon nanotube sheets in the absence of an applied field. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…While, sub-merged in 1 M H 3 PO 4 electrolyte, a 0.7 V (vs. SCE) constant potential was applied for 500 s, after which the electrode was immediately removed from the electrolyte. Zakhidov et al [36] showed that high double-layer charge densities can be retained after removing the sample from their electrolytes.…”
Section: Device Fabrication Of Awnp 800mentioning
confidence: 99%
“…While, sub-merged in 1 M H 3 PO 4 electrolyte, a 0.7 V (vs. SCE) constant potential was applied for 500 s, after which the electrode was immediately removed from the electrolyte. Zakhidov et al [36] showed that high double-layer charge densities can be retained after removing the sample from their electrolytes.…”
Section: Device Fabrication Of Awnp 800mentioning
confidence: 99%
“…With the help of simple solution‐processing (e.g., conformal coating, dipping, and drying), Hu et al have successfully fabricated CNT‐based commercial paper or textile energy devices (Figure 6g,h), which will bring new opportunities for advanced applications in energy storage and conversion 66–68. In addition, the CNT‐sheet supercapacitors are able to retain charge in the absence of contacting electrolyte, which greatly extends their charge‐storage times and is of significant importance in various applications 142. Nevertheless, different from the promising applications of transparent CNT films prepared through the solution‐processing and/or printing procedures described above, it is important to note that the potentials of CNT films fabricated by the direct CVD approach in the electronics and optoelectronics fields are still on the way.…”
Section: Applications Of Cnt Assembliesmentioning
confidence: 99%
“…8. This could be due to the so-called 'electrochemical doping' of the SWNTs at higher potentials [15,16]. The composite electrode fabricated using the host CNT network concept showed a similar rectangular shape with a higher specific capacitance provided by the high surface area aC particles.…”
Section: Electrochemical Characterizationmentioning
confidence: 98%